Older Subjects without Radiographic Knee Osteoarthritis: Weight, Height, and Body Mass Index - Fahlman, Lissa (JKL International LLC, 2013)
Osteoarthritis, the most common form of arthritis, conservatively affects 27 million American adults. While nearly all joints can be affected, knee osteoarthritis is of particular interest as it has the potential to severely limit mobility. Despite its ubiquity, not everyone is affected. Few studies on the characteristics of these persons exist. This descriptive paper examined older subjects without radiographic knee osteoarthritis (RKOA) at age 78, describing their height, weight and body mass index (BMI). Oldest subjects without RKOA at age 78 (n=143) were selected from the parent Clearwater Osteoarthritis Study, conducted from 1988–2009. Recalled weight and height for ages 25 and 45, as well as current weight and height were collected via questionnaire. Current measurements were also taken. BMI was derived. Absence of RKOA was determined using Kellgren-Lawrence criteria. Demographics: mostly female (72%), all Caucasian, better educated than the average US citizen, and more subjects lived with others. At all three life-stages, weights and BMI were lower, while heights were comparable to US 2000 figures. BMI was in the “normal” category at age 25 and in the “overweight” category at age 78. Weight was under reported and height was over reported, but by less than the general population. Both the increase in weight and decrease in height with age were statistically significant. Absence of RKOA appears to be related to lower weights, average heights, and lower BMI, relative to population norms at all three life-stages. These findings also suggest that the relationship may be more complicated. Higher BMI is ubiquitously recognized as a risk factor for RKOA, yet the average BMI of the subjects without RKOA was in the “overweight” category at age 78. A possible explanation may be an “inflated” BMI based on decrease in height, not just increase in weight.